UK Vessel Health and Preservation Framework 2020: a users' survey. (6th April 2023) - Hallam, Carole; Griffin, Hannah; Weston, Valya
Abstract : The review and update of the UK Vessel Health and Preservation Framework 2020 (VHP2020) was undertaken by a working group that included members of the Infection Prevention Society, the Royal College of Nursing, the National Infusion and Vascular Access Society and the Medusa Advisory Board and was launched in 2020. The VHP working group developed a survey to understand whether the VHP2020 had reached its intended audience, and what respondents thought were the benefits and drawbacks of its use in practice. Although the survey response was lower than expected, the responses received were largely positive and have provided feedback on how the VHP2020 is being used and some of the benefits. Most importantly, the survey has highlighted the need to communicate the benefits of the framework more effectively to reach a wider audience.